KARAKTERISASI ASAM AMINO DAN ASAM LEMAK RUMPUT LAUTPadina sp. DI MALANG RAPAT KABUPATEN BINTAN - Vister Efraim Amonio Gulo; Jumsurizal Jumsurizal; Aidil Fadli Ilhamdy (Fisheries Product Technology Department, Faculty of Marine Science and Fisheries, Universitas Maritim Raja Ali Haji, 2023)
Padina sp. is a species of brown seaweed (Phaeophyta). Padina sp seaweed grows wild in the waters. Malangrapat waters in Bintan Regency are one of the habitats for Padina sp. This study aimed to observe the proximate content as well as amino acids and fatty acids in Padina sp. in order as a reference to maximize the utilization of Padina sp. The water content of Padina sp. 13.87%, ash content 39.41%, fat content 2.67%, protein content 5.94%, and carbohydrate content 38.12%. Meanwhile, the highest amino.acid content in Padina sp. Glutamic.acid has a value of 7640.89 + 10.20 mg/kg, Aspartic acid has a value of 6926.39 + 9.05 mg/kg, and Leucine has a value of 4223.59 + 1.68 mg/kg. As well as for the fatty acid content with the highest levels in brown seaweed Padina sp. are 1.55% saturated fat and unsaturated fatty acids which have a value of 1.11%.